Analysis of the Effect of Optimization of Electricity Consumption Control (P2TL) on the Reduction of Non-Technical Shrinkage in PT. PLN (Persero) ULP Sukadana - Zarina Dwi Angelica; Hamdani Hamdani; Dian Yulis Wulandari (Sean Institute, 2026)
This study aims to analyze the effect of optimizing the Electricity Usage Control Program (Penertiban Pemakaian Tenaga Listrik – P2TL) on the reduction of non-technical losses at PT PLN (Persero) ULP Sukadana. Non-technical losses are generally caused by electricity theft, meter reading errors, and misuse of customer installations, which can lead to significant financial losses for the company. The research employed a quantitative approach, with data collected through documentation, field observations, and interviews with P2TL officers. Data analysis was conducted using linear regression to determine the relationship between the effectiveness of the P2TL program and the level of non-technical loss reduction. The results indicate that P2TL optimization has a positive and significant effect on reducing non-technical losses. Improvements in P2TL effectiveness, such as increased inspection intensity, the use of more accurate detection equipment, and stricter enforcement of sanctions for violations, were proven to reduce energy losses. These findings confirm that a well-managed P2TL program can serve as an effective strategy for PLN to enhance operational efficiency and minimize losses resulting from non-technical factors.